Effect of an Educational Program on Healthcare Professionals’ Readiness to Support Patients with Asthma, Allergies, and Chronic Obstructive Lung Disease for Improved Medication Adherence - Malin Axelsson; Benita Björk; Ulrika Berg; Karin Persson (Nursing Research and Practice)
Purpose. The aim of this study was to strengthen the healthcare professionals’ readiness to support patients who have asthma, an allergy, and COPD for better medication adherence. Methods. The design was an educational intervention in a study population (n = 70) consisting of 66 nurses and four other allied healthcare professionals working in primary care with patients diagnosed with asthma, allergy, or COPD in a county in southern Sweden. As part of two training days, an educational intervention—consisting of lectures and workshops—was conducted. Both qualitative and quantitative data were collected. The qualitative data were collected during the workshops when the participants worked with fictitious patient cases. They documented in writing how they, based on the theoretical content in the educational intervention in combination with their clinical experiences, reasoned that the fictitious patients could be supported for better adherence. This documentation constituted qualitative data. The quantitative data were collected through questionnaires, which the participants completed before and after the intervention. Data from the questionnaires were statistically analyzed using descriptive statistics and paired t-tests. The qualitative data collected from the workshops were analyzed with content analysis. Results. The intervention increased the participants’ knowledge of adherence (pre mean 3.95 versus post mean 4.18, p=0.001) and how to better support patients’ adherence to medication (pre mean 3.71 versus post mean 3.98, p=0.001). Moreover, their knowledge of how to measure patients’ adherence behavior (pre mean 3.02 versus post mean 3.54, p=0.001) and how to communicate with patients effectively about adherence was heightened (pre mean 3.92 versus post mean 4.13, p=0.011). Furthermore, participants felt that their readiness to support patients for better adherence had strengthened (pre mean 3.78 versus post mean 4.13, p=0.001). Individual adherence support for three fictitious patients with different adherence issues was developed. Conclusion. An educational intervention focusing on adherence and communication equipped healthcare professionals with tools to support patients with asthma, an allergy, or COPD for better medication adherence.